Farmer adoption of irrigation water conservation measures in the South Platte River Basin - Smith, Dan H., author; Klein, Kathleen C., author; Ward, Robert C., author; U.S. Committee on Irrigation and Drainage, publisher (Colorado State University. Libraries, 1996)
The potential of demand management as a water management tool in the South Platte River basin is limited by a lack of information regarding existing irrigation practices. A study was conducted to obtain information regarding irrigation water use practices in the basin, to determine the frequency of adoption of water conservation practices, and to relate the frequency of adoption of water conserving measures to various demographic factors. The results were based on 285 responses to a voluntary survey sent to a random sample of 1000 irrigators in eight counties within the basin during the winter of 1995. The survey sought information on farming practices, the adoption of water conservation practices, and grower characteristics. Although disincentives for irrigation water conservation appeared to be significant, the results indicated a high rate of adoption. Seventy-four percent of the survey respondents had adopted some type of water conservation measure on their farms. Adoption of various irrigation water conservation practices was associated most frequently with farm size, but factors such as method of irrigation, water source, knowledge of water law, and level of education were also associated with adoption of one or more conservation measures. Respondents indicated that the primary incentive for adopting water conservation measures was "water conservation." The typical reason for conserving water was to improve existing operations. This suggests that in many instances conservation is being used as a method of extending existing supplies on farms operating under water-short decrees.
1996 USCID water management conference
South Platte River Basin
Not digitized by CSUL Digital Services.
Presented at Competing interests in water resources - searching for consensus: proceedings from the USCID water management conference held on December 5-7, 1996 in Las Vegas, Nevada.